Economic Knock-On Effects of Russia's Geopolitical Risk on Advanced Economies: A Global VAR Approach - Boris Blagov; Maximilian Dirks; Michael Funke (Center for Economic Studies and ifo Institute (CESifo), 2024)
Using Russia as a case study and a global VAR model as a methodological tool, we analyze how heightened geopolitical risk shocks propagate across advanced economies and quantify the economic effects of these events. The global VAR impulse response functions in response to the skyrocketing Russian geo-political risk shock after Russia's invasion of Ukraine revealed a contraction of GDP and an increase in inflation. Eastern European neighboring countries are particularly affected by the Russian geopolitical risk shock. We also document a strong component of the Russian geopolitical risk shock that is not driven by fossil fuel prices.
Keywords: C32; E32; F51; F52; 330; geopolitical risk; international business cycle transmission; global VAR model; Russia